Improved Security Patch on Secure Communication among Cell Phones and Sensor Networks - Ndibanje Bruce; Tae-Yong Kim; Hoon Jae Lee (International Journal of Distributed Sensor Networks)
The communication between cell phones and sensor networks involves strong user authentication protocols to ensure the data and network security. Generally, in order to obtain the relevant information, cell phones interact with sensor networks via gateways. In 2009, according to Arjan Durresi and Vamsi Paruchuri scheme, this unique ability is used to provide better authentication and security protocols that can be used to establish secure communications among cell phones and sensor networks. In this paper, we show that their scheme is vulnerable to known attacks such as man-in-the-middle attack and reply attack, and it does not provide mutual authentication between gateway node and cell phone. In addition, it does not establish session key after the authentication phase. To fill this security gap, we proposed security patches and improvements, which overcome the weak features in the scheme of Arjan Durresi and Vamsi Paruchuri. Finally, we came out with results which show that our improved security patch establishes trust between the cell phone and gateway in the form of mutual authentication and provides the session key establishment after the authentication phase.